Les régions françaises dans le millefeuille institutionnel des politiques de développement numérique - Charlotte Ullmann (Netcom)
As the liberalisation of the telecommunications sector and the decentralisation of local competences take effect, digital development sets out a new “challenge” for local authorities faced with territorial competition. Regions can consider ICT (Information and Communication Technology) as an opportunity, not just to reinforce their role among other local authorities but also to create efficient strategies. To address this hypothesis, the method chosen is based on the study of three French regions : Alsace, Midi-Pyrénées and Picardie in order to understand the reasons for regional involvement, to analyse regional strategic frameworks, and estimate the part played by regions.